PENGARUH DIGITAL MARKETING DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN PADA STARTUP BIKE RENTAL BANANAZ BALI - Alicia Sastra Millenium; I Wayan Suardana; I Made Kusuma Negara (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2021)
The increase in international tourist every year on the island of Bali is used by tourism entrepreneurs to help the government increase regional and the state revenues. The need for transportation for travel activities provides an opportunity for Bananaz Bali to launch the first rental application in Bali. Based on Start-up, Bananaz Bali applies digital marketing and is also assisted by implementing brand awareness activities. This study requires 75 respondents with the criteria of over the age of 18 years old, and have already used Bananaz Bali services. All the data collected through questionnaires and then processed using data analysis techniques SEM Partial Least Square. The results of this study are: 1) There is a positive and significant relationship between digital marketing variable and brand awareness. 2) There is a negative and insignificant relationship between digital marketing variable on purchasing decisions. 3) Against a positive and significant relationship between brand awareness and purchasing decisions.